MODERN ECOLOGICAL CULTURE OF THE UZBEKS OF THE KHORAZM OASIS - Egamberganova Matluba Jobborgonovna (Journal of Social Sciences and Humanities Research Fundamentals, 2024)
This article presents information about the ecological problems of the Khorezm oasis and the ecological culture of the oasis residents in order to prevent them. ‎